Assessment of a Uasb Reactor with High Ammonia Concentrations: Effect of Zeolite Addition on Process Performance - Huilinir-Curio, C; Montalvo-Martinez, S (Elsevier Ltd, 2014)
The UASB process for wastewater treatment has been extensively studied, but the use of zeolite to improve UASB reactor performance has rarely been explored. In this study, a UASB reactor modified with natural zeolite operating at high nitrogen concentrations (0.5, 0.7 and 1 g/L) was evaluated. Two laboratory bioreactors, one with zeolite and one without, were operated at ambient temperatures ranging between 18 °C and 21 °C. The experimental phase had a start-up period of 21 days. In the reactor with zeolite, the pH was found to be between 7.9 and 9.1, with a COD removal efficiency of about 60% after 80 days of operation at ammonia concentrations of between 0.229 and 0.429 g/L in the effluent. In the reactor without zeolite, the pH was between 8.3 and 9.3, and the COD removal efficiency was about 40% at ammonia concentrations between 0.244 and 0.535 g/L in the effluent. The addition of zeolite also decreased the volatile suspended solids (VSS) concentration in the effluent, generating a biomass with larger granules and higher settling rates as compared to a UASB reactor without zeolite. Taking the lower ammonia concentration, the higher COD removal and the improved granulation into account, it can be concluded that natural zeolite positively influenced the behavior and performance of the UASB reactor operating with high nitrogen concentrations. © 2014 Elsevier Ltd.